I have the equation:

e=(a*c*d)-(d*(b-a))

and need to make d the subject?! (Worried)

Cheers,

Sam

Printable View

- September 16th 2010, 05:52 AMsammycRe-arranging formula
I have the equation:

e=(a*c*d)-(d*(b-a))

and need to make d the subject?! (Worried)

Cheers,

Sam - September 16th 2010, 05:55 AMUnknown008
1. Expand d(b-a) first.

2. Expand -(d(b-a)) then.

3. Factorise all the d's

4. Divide by something to get d alone. - September 16th 2010, 06:02 AMJoel
expand first bracket

e = acd - (d*(b-a))

expand second bracket

e = acd -db + da

divide both sides by d

e/d = ac - b + a

flip both sides

d/e = 1 / ac - b + a

multiply both sides by e

d = e / ac - b + a - September 16th 2010, 06:05 AMsammyc
Awesome, thanks Joel